PENGARUH KECERDASAN SPIRITUAL TERHADAP ETIKA PROFESI AUDITOR PADA INSPEKTORAT KOTA KENDARI - Umar, Missi R (JURNAL AKUNTANSI, 2016)
This research aimed of presented to examine the effect of spiritual intelligence on the professional ethics of auditors. Primary data in this research were obtained from the perception of all employees with functional positions in the scope of the Inspectorate of Kendari. Perceptions of respondents was measured by responses to questionnaires that uses ordinal measurement with a 5-point Likert scale. The analytical tool used to test the hypothesis is simple linear  regression analysis.The results of this research  indicate that spiritual intelligence significantly effect on the professional ethics of auditors. The results of the coefficient of determination for spiritual intelligence is  R2 = 0,813. This number can be used to see the contribution of spiritual intelligence  on the professional ethics of auditors. The figure has meaning that the contribution of spiritual intelligence on the professional ethics of auditors is 81,3%, while the remaining 18,7% was obtained from the contribution of other factors. Keywords: Spiritual Intelligence, Professional Ethics of Auditors.